Crises de imagem na mídia proposta de guia de prevenção e análise para agentes políticos - Grôppo, Leandro Barreto (2015)
It is common for political crises to concern only when they are already installed or in the process of being exposed, causing reactive actions of limited consequences. The actual increasing occurrence of cases tends to become a self-reproductive process, with focus and media attention, leading to reduced social trust, in which the legitimacy of institutions and politicians depends on. Besides creating a skepticism\'s environment in public opinion, it exacerbates the weakness climate of representative democracy. Despite the great crises amount of several kinds involving politicians in the history, there is a shortage literature on this subject, especially with regard of analytical and practical way that aims to mitigate and even avoid such situations. Against this backdrop, the present work is related, in order to provide the society, especially on the political and political and communication\'s professionals, knowledge and information to be used in real cases, through an implementation plan, in practical guide format that collaborate with the social dynamics on the atypical emotional environment of the crises\'s image. With the special purpose of promoting the prevention of attitude so that crises do not occur; and, if in case of them to be inevitable, to have the least impact as possible on the political agent image and at the institution which can be related on, it is used throughout the text several examples to provide various application possibilities in various possible occurrence\'s types. Within the functional aspect of the proposal, the phases are shown to be overcome in crisis management planning, together with analytical factors to be raised, as instruments of prevention and analysis of politicians crisis image in the media. To become able the stability of democratic system with behavior changing of its actors, with respect to zeal for the reputation and consequently making practice and cultivation of positive social values. Paths that can be covered to assist in sustaining the confidence of political leadership, mandates and governments.